2006
DOI: 10.1080/08856250600956162
|View full text |Cite
|
Sign up to set email alerts
|

Factors correlated with teachers’ attitudes towards the inclusion of students with special educational needs in Cyprus

Abstract: Inclusion of SEN students in mainstream classrooms constitutes an ambitious objective of the education system in Cyprus. The legislation currently in effect provides for a clear-cut frame of action, largely based on the willingness of teachers in the mainstream school, who are expected to develop positive attitudes that encourage and support the coeducation of SEN and non-SEN students. However, the impact of infrastructural insufficiency, prejudice and, above all, the lack of specific knowledge as regards spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
11

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 20 publications
3
36
0
11
Order By: Relevance
“…In an interesting permutation of inclusive practices, Koutrouba, Vamvakari, and Steliou (2006) reported that in Cyprus, a small percentage of children with mild disabilities receive adapted instruction in special classes within general education. Students with severe disabilities attend special schools, strategically built within the compounds of the general education school buildings, whereas the vast majority of students with mild SEN are fully included in general education schools.…”
Section: Variations In Inclusive Educational Practicesmentioning
confidence: 98%
See 1 more Smart Citation
“…In an interesting permutation of inclusive practices, Koutrouba, Vamvakari, and Steliou (2006) reported that in Cyprus, a small percentage of children with mild disabilities receive adapted instruction in special classes within general education. Students with severe disabilities attend special schools, strategically built within the compounds of the general education school buildings, whereas the vast majority of students with mild SEN are fully included in general education schools.…”
Section: Variations In Inclusive Educational Practicesmentioning
confidence: 98%
“…The lack of training opportunities is also consistently associated with negative reception of inclusion across different school systems. Teachers in Cyprus experience mistrust towards inclusion largely due to a lack of graduate training in special education (Koutrouba, Vamvakari, & Steliou, 2006).…”
Section: Teachers' Concerns About Inclusionmentioning
confidence: 99%
“…Moreover, there is great evidence in the literature that providing schools with adequate and appropriate resources and materials, adapting teaching materials, restructuring the physical environment to be accessible to students with physical disabilities and reducing class size are instrumental in the development of teachers' positive attitudes (Clough & Lindsay, 1991;Janney et al, 1995;Koutrouba et al, 2006;LeRoy & Simpson, 1996).…”
Section: School-related Variablesmentioning
confidence: 99%
“…In their study of factors affecting teachers' attitudes towards inclusion in Cyprus, Koutrouba et al (2006) argued that addressing infrastructural and specialized staff shortages in schools is very important, as this shortage is a major cause of mistrust among teachers towards inclusion efforts. They added that providing equipment to schools with appropriate ramps and lifts, supplying Braille machines and closed-circuit television systems (for students with visual impairment), providing headphones and special microphones and the staffing of schools with sign language users and speech therapists (for students with hearing and speech disabilities) could significantly reverse teachers' negative attitudes.…”
Section: School-related Variablesmentioning
confidence: 99%
“…Another important aspect of inclusive classrooms is that they maintain the same standards for all pupils, and this can be ensured through the promotion of interactive and group work (Stevens and Slavin 1995;Stainback and Stainback 1996;Porter 1997;Blatchford et al 2003;Meijer et al 2003;Koutrouba et al 2006). All of these inclusive strategies are implemented in heterogeneous groupings.…”
Section: Streamingmentioning
confidence: 99%